2007
DOI: 10.1016/j.febslet.2007.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Two isoforms of chicken melanopsins show blue light sensitivity

Abstract: Melanopsin is a vertebrate non-visual opsin and functions as a circadian photoreceptor in mammalian retinas. Here we found the expression of two kinds of melanopsin genes in the chicken pineal gland and identified the presence of five isoforms derived from these two genes. Reconstitution of the recombinant proteins with 11-cis-retinal revealed that at least two of these melanopsin protein isoforms can function as blue-sensitive photopigments with absorption maxima at 476-484 nm. These values are consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 31 publications
5
73
0
5
Order By: Relevance
“…Bellingham et al (2006) did not detect OPN4x mRNA in adult Xenopus skin tissue, which may be due to the low quantity of OPN4x mRNA, as it is only expressed in stitches, or it might indicate that the two strong bands we observe in stitch samples represent two splice variants of OPN4m. This phenomenon has already been observed in some mammalian species (Pires et al, 2009), such as the chicken (Torii et al, 2007), and in the elephant shark (Davies et al, 2012). The immunoreactivity at higher molecular masses is consistent with the formation of oligomeric complexes (dimers, trimers etc.…”
Section: Resultssupporting
confidence: 58%
“…Bellingham et al (2006) did not detect OPN4x mRNA in adult Xenopus skin tissue, which may be due to the low quantity of OPN4x mRNA, as it is only expressed in stitches, or it might indicate that the two strong bands we observe in stitch samples represent two splice variants of OPN4m. This phenomenon has already been observed in some mammalian species (Pires et al, 2009), such as the chicken (Torii et al, 2007), and in the elephant shark (Davies et al, 2012). The immunoreactivity at higher molecular masses is consistent with the formation of oligomeric complexes (dimers, trimers etc.…”
Section: Resultssupporting
confidence: 58%
“…However, one group again reported a melanopsin absorption maximum ~420 nm (Melyan et al 2005) whereas the others indicated that expressed melanopsin maximally absorbed light at ~480 nm (Panda et al 2005;Qiu et al 2005), matching more closely the spectral tuning of pharmacologically isolated rat (Berson et al 2002) and primate (Dacey et al 2005) ipRGCs. It should be noted that non-mammalian melanopsin also shows peak spectral sensitivity ~480 nm, in close agreement with mammalian ipRGCs (Koyanagi et al 2005;Torii et al 2007;Davies et al 2011). Thus, it is now generally agreed that mammalian melanopsin maximally absorbs light at ~480 nm although direct in vitro spectroscopic analysis of purified mammalian melanopsin is still needed (Bailes and Lucas 2010).…”
Section: Melanopsin Is a Photopigmentmentioning
confidence: 94%
“…The dissimilarity in findings among these three different rodents may represent true species differences, but it remains to be demonstrated using physiological techniques that the "non-melanopsin" SCN-projecting RGCs identified in the rat and golden hamster are not intrinsically light sensitive. It is possible that these RGCs either express too little melanopsin to be detected (Baver et al 2008;Ecker et al 2010) or express a melanopsin isoform not recognized by the antibodies currently available (Torii et al 2007;Pires et al 2009;Davies et al 2011). The number of "non-melanopsin" RGCs sending afferent fibers to the SCN in the golden hamster and rat is small (i.e., 100-200) making the task of recording from these cells difficult.…”
Section: P I C K a R D And S O L L A R S I N R E V P H Y S I O L B I O mentioning
confidence: 99%
“…Since OPN4 is known to have an important role in light transmission through the eyes, and on the other hand, OPN4 is shown to be expressed in the hypothalamus [27], it may be capable of activating circadian signaling pathways directly by transcranially penetrated light, although we acknowledge that there might be some light transmitted through the transcranially illuminated ocular photoreceptors [49,50]. Even though the absorption maximum of our light source (450 nm) [20] was not optimal for the OPN4 expression maximum (476 -484 nm) [51,52], we were able to obtain significant results in this study.…”
Section: Discussionmentioning
confidence: 86%